2005
DOI: 10.1083/jcb.200502141
|View full text |Cite
|
Sign up to set email alerts
|

RanBP3 enhances nuclear export of active β-catenin independently of CRM1

Abstract: β-Catenin is the nuclear effector of the Wnt signaling cascade. The mechanism by which nuclear activity of β-catenin is regulated is not well defined. Therefore, we used the nuclear marker RanGTP to screen for novel nuclear β-catenin binding proteins. We identified a cofactor of chromosome region maintenance 1 (CRM1)–mediated nuclear export, Ran binding protein 3 (RanBP3), as a novel β-catenin–interacting protein that binds directly to β-catenin in a RanGTP-stimulated manner. RanBP3 inhibits β-catenin–mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 79 publications
(91 reference statements)
3
81
0
Order By: Relevance
“…For nuclear export of β-catenin there is evidence that β-catenin may exit via binding to proteins such as Axin (12) and APC (10) using a Ran and CRM1-independent mechanism (11). Alternatively, β-catenin can interact with RanBP3 to be exported from the nucleus (14). In the present work we show that Custos inhibits canonical Wnt signaling in frog embryos and cultured cells by antagonizing nuclear import of β−catenin.…”
supporting
confidence: 48%
“…For nuclear export of β-catenin there is evidence that β-catenin may exit via binding to proteins such as Axin (12) and APC (10) using a Ran and CRM1-independent mechanism (11). Alternatively, β-catenin can interact with RanBP3 to be exported from the nucleus (14). In the present work we show that Custos inhibits canonical Wnt signaling in frog embryos and cultured cells by antagonizing nuclear import of β−catenin.…”
supporting
confidence: 48%
“…Knockdown of WEE1 promotes G2/M progression and sensitizes stathmin-overexpressing breast cancer cells to paclitaxel and vinblastine [48]. RANBP3 ablation causes overactivation of Wnt signaling pathway, and the chromosome region 19p13.3 containing the RANBP3 gene is deleted in various types of cancers and may contain tumor suppressor gene [49]. Three promising genes (LTBR, EI24 and SMAD2) were identified as targets of miR-455-3p.…”
Section: Discussionmentioning
confidence: 99%
“…115,116 Furthermore, RanBP3 has been shown to be involved in nuclear export of ␤-catenin. 117 In the nucleus, Bcl9 and pygopus play a role in retention of ␤-catenin. 118 In detailed fluorescence recovery after photobleaching experiments, it was recently shown that APC, axin, Bcl9, and TCF factors influence the cytoplasmic/nuclear localization of ␤-catenin mainly on the level of retention rather than active transport.…”
Section: Regulating Nuclear Localization Of ␤-Cateninmentioning
confidence: 99%